Discovery of the first chemical tools to regulate MKK3-mediated MYC activation in cancer. (1st September 2021) - Yang, Xuan; Fan, Dacheng; Troha, Aidan Henry; Ahn, Hyunjun Max; Qian, Kun; Liang, Bo; Du, Yuhong; Fu, Haian; Ivanov, Andrey A.
Graphical abstract: Abstract: The transcription master regulator MYC plays an essential role in regulating major cellular programs and is a well-established therapeutic target in cancer. However, MYC targeting for drug discovery is challenging. New therapeutic approaches to control MYC-dependent malignancy are urgently needed. The mitogen-activated protein kinase kinase 3 (MKK3) binds and activates MYC in different cell types, and disruption of MKK3-MYC protein–protein interaction may provide a new strategy to target MYC-driven programs. However, there is no perturbagen available to interrogate and control this signaling arm. In this study, we assessed the drugability of the MKK3-MYC complex and discovered the first chemical tool to regulate MKK3-mediated MYC activation. We have designed a short 44-residue inhibitory peptide and developed a cell lysate-based time-resolved fluorescence resonance energy transfer (TR-FRET) assay to discover the first small molecule MKK3-MYC PPI inhibitor. We have optimized and miniaturized the assay into an ultra-high-throughput screening (uHTS) 1536-well plate format. The pilot screen of ~6, 000 compounds of a bioactive chemical library followed by multiple secondary and orthogonal assays revealed a quinoline derivative SGI-1027 as a potent inhibitor of MKK3-MYC PPI. We have shown that SGI-1027 disrupts the MKK3-MYC complex in cells and in vitro and inhibits MYC transcriptional activity in colon and breast cancer cells. In contrast, SGI-1027 does not inhibit MKK3 kinase activity and does not interfere with well-known MKK3-p38 and MYC-MAX complexes. Together, our studies demonstrate the drugability of MKK3-MYC PPI, provide the first chemical tool to interrogate its biological functions, and establish a new uHTS assay to enable future discovery of potent and selective inhibitors to regulate this oncogenic complex.